2004
DOI: 10.1097/01.asn.0000143473.64430.ac
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Multidrug Resistance Protein 2 (MRP2/ABCC2) to the Renal Excretion of p-aminohippurate (PAH) and Identification of MRP4 (ABCC4) as a Novel PAH Transporter

Abstract: Abstract. p-Aminohippurate (PAH) is the classical substrate used in the characterization of organic anion transport in renal proximal tubular cells. Although basolateral transporters for PAH uptake from blood into the cell have been well characterized, there is still little knowledge on the apical urinary efflux transporters. The multidrug resistance protein 2 (MRP2/ ABCC2) is localized to the apical membrane and mediates ATP-dependent PAH transport, but its contribution to urinary PAH excretion is not known. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
74
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(80 citation statements)
references
References 43 publications
4
74
0
Order By: Relevance
“…Previous studies have identified several organic anions that inhibit one MRP transporter while stimulating another, leading to the conclusion that some MRPs contain at least two interacting ligand binding sites (Bakos et al, 2000;Zelcer et al, 2003;Wittgen et al, 2011). For example, both sulfinpyrazone and probenicid inhibit MRP1 and MRP4 but stimulate MRP2 (Bakos et al, 2000;Ito et al, 2001a;Smeets et al, 2004;Huisman et al, 2005). Consequently, the opposite effects observed for CGP V-4 and V-6 on MRP1 (inhibitory) versus MRP2 (stimulatory) are in themselves not surprising.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have identified several organic anions that inhibit one MRP transporter while stimulating another, leading to the conclusion that some MRPs contain at least two interacting ligand binding sites (Bakos et al, 2000;Zelcer et al, 2003;Wittgen et al, 2011). For example, both sulfinpyrazone and probenicid inhibit MRP1 and MRP4 but stimulate MRP2 (Bakos et al, 2000;Ito et al, 2001a;Smeets et al, 2004;Huisman et al, 2005). Consequently, the opposite effects observed for CGP V-4 and V-6 on MRP1 (inhibitory) versus MRP2 (stimulatory) are in themselves not surprising.…”
Section: Discussionmentioning
confidence: 94%
“…The wide range of drug substrates includes antibiotics, antivirals, and diuretics (8). In comparison to MRP2, MRP4 exhibits a higher expression in the kidney and a higher affinity for smaller organic anions (25). Polymorphisms in ABCC2 and ABCC4, leading to diminished MRP2 or MRP4 activity, respectively, are associated with increased sensitivity to nephrotoxicity or delayed graft function after kidney transplantation (26,27).…”
Section: Multidrug Resistance Proteinsmentioning
confidence: 99%
“…Both transporters accept a variety of organic anions as substrates, such as p-aminohippurate (PAH), 17␤-estradiol-17␤-d-glucuronide, dehydroepiandrosterone sulfate (DHEAS), and methotrexate (18,(25)(26)(27). van Aubel et al (18) initially found that Mrp4 is localized on the BBM, and, subsequently, Mrp4 was suggested to play important roles in tubular secretion (18,25,28), although direct evidence of this still is lacking. For BCRP, an in vivo study using Bcrp knockout mice has demonstrated that BCRP is responsible for the urinary excretion of some organic anions, such as methotrexate and 6-hydroxy-5,7-dimethyl-2-methylamino-4-(3-pyridylmethyl) benzothiazole (E3040) sulfate (29,30).…”
mentioning
confidence: 99%